Someone Builds the Dream - Wheeler, Lisa, 1963-; Long, Loren (New York : Dial Books for Young Readers, 2021)
Celebrates the skilled women and men who work to see the plans of architects, engineers, and designers brought to life.
Keywords: Building -- Juvenile fiction; Construction workers -- Juvenile fiction; Stories in rhyme; Building -- Fiction; Construction workers -- Fiction